(untitled) (De Musica, 2024)
Various music enthusiasts can testify from personal experience to the powerful impact of listening to sad music, and several experimental studies have confirmed the widespread preference for this musical genre. Sadness is a negative emotion, and if someone seeks it out in real life, they are considered to be suffering from some psychological disorder. So why is the avid listener of sad music not usually a psychopath? This study attempts a reconnaissance of the various hypotheses that have been put forward, and the ensuing discussions, about the paradox of enjoying sadness in music. Ending with the observation that we are still far from a convincing explanation.